About the unidirectionality of interference: Insight from the musical Stroop effect. - Grégoire, Laurent; Perruchet, Pierre; Poulin-Charronnat, Bénédicte (Quarterly Journal of Experimental Psychology, 2014)
The asymmetry of interference in a Stroop task usually refers to the well-documented result that incongruent colour words slow colour naming (Stroop effect) but incongruent colours do not slow colour word reading (no reverse Stroop effect). A few other studies have suggested that, more generally, a reverse Stroop effect can be occasionally observed but at the expense of the Stroop effect itself, as if interference was inherently unidirectional, from the stronger to the weaker of the two competing processes. We describe here a situation conducive to a pervasive mutual interference effect. Musicians were exposed to congruent and incongruent note name/note position patterns, and they were asked either to read the word while ignoring the location of the note within the staff, or to name the note while ignoring the note name written inside the note picture. Most of the participants exhibited interference in the two tasks. Overall, this result pattern runs against the still prevalent model of the Stroop phenomenon [Cohen, J. D., Dunbar, K., & McClelland, J. L. (1990). On the control of automatic processes: A parallel distributed processing account of the Stroop effect.Psychological Review,97(3), 332–361]. However, further analyses lend support to one of the key tenets of the model, namely that the pattern of interference depends on the relative strength of the two competing pathways. The reasons for the impressive differences between the results collected in the present study and in the standard colour–word (or picture–word) paradigms are also examined. We suggest that these differences reveal the importance of stimulus–response contingency in the formation of automatisms.